Social Stigma and Awareness About Hearing Aids in India - Gupta, Aarti (Digital Repository of Theses - SSBM Geneva, 2025)
The study aims to examine hearing aid stigma and awareness in India. The main objective of the study is to focus on the causes of hearing aid stigma in India and find measures to promote the use of these devices. The study used mixed method to examine hearing aid perceptions, attitudes, and knowledge using qualitative interviews and questionnaires. Qualitative interviews reveal hearing-impaired people’s lives, whereas surveys reveal society’s views on Hearing aids. The sample of the study includes hearing-impaired people, healthcare experts, and the general population in order to collect varied perspectives. The findings of the study shows that Hearing aids are stigmatized in India, resulting in low knowledge and acceptance among hearing-impaired people. Reluctance to wear Hearing aids stems from misconceptions about old age and infirmity. However, hearing loss and hearing aid benefits for overall well-being are becoming more widely recognized. The study also highlights the requirement for targeted awareness initiatives and educational activities to reduce the stigma associated with Hearing aids and promote their adoption in India. These findings can help hearing aid companies sell Hearing aids positively and encourage hearing loss patients to utilize them. For people with hearing impairments in India, companies can make it easier for them to get Hearing aids and improve their quality of life by fighting social stigma and raising awareness.